The influence of (beta) technology intensity and evaluating TCC using aHP model in Iran Tractor Manufacturing Company (ITMCO) - Golzari Nezhad, Shahryar Ghorbani (Zia World Press, 2010)

(untitled)
Due to the strategists in business World, the most important strategic consideration in international economic and industrial competition is in managing innovation and technology context. Increasing the competitive advantage of each economic institution needs the increase of technologic content improvement applied in production process of that institution. The present paper aims to study and evaluate the technology intensity and TCC in Iran Tractor Manufacturing Company (ITMCO). According to the results of research work, the authors have offered proposals to improve the technology by introducing the turning points and defects existed in technology parts in the company.